Effective Audit Procedures: Is It Auditor's Characters and Proffesional Sceptism Matters? - Aisyaturrahmi (AKRUAL: JURNAL AKUNTANSI, 2021)
The aim of this study is to examine the auditors characteristics and the selection of effective audit procedures by introducing professional scepticism as an intervening variable. In this study the author focuses on gender, experience and personality type. We examine to what extent such characteristics influence the selection of effective audit procedures. We conducted a survey for practitioners who actively work in the public accountant firms in East Java province. The results show that professional scepticism which is treated as an intervening variable do not play role on the relationships between gender and experience and the selection of effective audit procedures. In contrast, it help us to explain the relationships between personality type and the selection of effective audit procedures